A Topology Controlling Scheme Based on Guard Region in Wireless Sensor Network. (31st May 2016) - Wang, Xiaojuan; Kang, Lin; You, Jingwen; Song, Mei
Abstract : In dense wireless sensor network, we usually remove the unnecessary communication links by topology control in order to get an energy efficient routing. The channel environment becomes more complex, which results in difficulty to control topology under a mass node distribution according to the accurate interference model. This paper introduces the concept of a guard region, defined as the region around each receiver where interfering transmissions are inhibited to make the topology control. Based on the hard-core process in stochastic geometry, the scheduling of interfering node in guard region and the density of active sensors are achieved theoretically. Then we do the analysis of coverage of receiver; the interference around receiver is computed as main interference in guard region and secondary interference outside guard region. Finally, through Monte-Carlo simulation, the topology model based on guard region is proved to be correct and the influences on coverage under different parameters are analyzed.